Innovative Financial Planning Strategies in The Digital Landscape at Ngo Permai Penang - HIDAYAH, Nurul; UTAMI, Fransisca L; RAHMAT, Khozaeni Bin; ALI, Anees Janee; ASHAR, Zubir (Indonesia Strategic Sustainability, 2025)
In the digital landscape, financial planning strategies must strike a balance between leveraging technology and managing the risks associated with it. By embracing digital advances while ensuring security, compliance, and personalized service, financial planners can drive better financial outcomes and create long-term value for PKS and NGO. Pertubuhan Masyarakat Indonesia (PERMAI) Penang is an Indonesian community organization in Penang, Malaysia. It is an NGO or non-governmental organization, meaning it is not part of the government. PERMAI Penang was officially registered with the Malaysian Organization Registration (Register of Society/ROS) in 2019, bearing the registration number 006-07-04022019.PERMAI Penang operates within the social sector, working in the social, educational, and cultural domains. The NGO's membership includes Malaysian and Indonesian individuals residing in Malaysia, including professionals, workers, students, and scholars.PERMAI's primary objectives are to promote educational opportunities for Indonesian children in Malaysia and to equip individuals with marketable skills, thereby enhancing their employability and earning potential. The community service team from UMB has been conducting educational sessions on financial planning, recognizing the importance of financial management in the modern digital economy. It is essential to comprehend and implement the contemporary facets of financial planning within the context of the evolving digital economy. The output of this PKM activity is to improve the value system in the community to develop awareness of the need to improve financial literacy, especially for MSME players, and endeavor will offer scientific discernment on financial management in business.